2022
DOI: 10.2196/28091
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative User Data From a Chatbot Developed for Women With Gestational Diabetes Mellitus: Observational Study

Abstract: Background The rising prevalence of gestational diabetes mellitus (GDM) calls for the use of innovative methods to inform and empower these pregnant women. An information chatbot, Dina, was developed for women with GDM and is Norway’s first health chatbot, integrated into the national digital health platform. Objective The aim of this study is to investigate what kind of information users seek in a health chatbot providing support on GDM. Furthermore, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Based on a 20-week data collection, the authors reported that the chatbot could answer 89% of almost 3,000 questions, providing women with readily accessible information about their condition. 12 Integration of such applications in national digital health platforms governed by the public sector might increase public trust needed for successful implementation. Considering the dominance of the private sector in the field of AI, and that people are more willing to share their data for AI research with the public sector than with private companies, 13 it is relevant to make partnerships between different actors and stakeholders, and patient organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a 20-week data collection, the authors reported that the chatbot could answer 89% of almost 3,000 questions, providing women with readily accessible information about their condition. 12 Integration of such applications in national digital health platforms governed by the public sector might increase public trust needed for successful implementation. Considering the dominance of the private sector in the field of AI, and that people are more willing to share their data for AI research with the public sector than with private companies, 13 it is relevant to make partnerships between different actors and stakeholders, and patient organizations.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, the first chatbot integrated into the national health service platform was developed to inform and empower women with gestational diabetes. 12 Our previous work suggests that the majority of patients are open to AI-based solutions, with higher acceptance rates in low-risk situations. 13 This calls for studies investigating the knowledge and value of large language models, such as ChatGPT, in everyday, practical scenarios and routine clinical care.…”
Section: Introductionmentioning
confidence: 99%
“…15,30,37,[39][40][41]43,45 Overall, participants were satisfied and felt that chatbots were able to deliver "trustworthy information" 31 and answer the majority of their questions. [14][15][16]30,43 Although participants knew that the chatbot was computer generated, some treated it like their "mum," health care professional, friend, or confidante and recounted personal anecdotes while interacting with the chatbot. 14,31,42 Host of Health Benefits Chatbots were able to improve participants' health outcomes holistically.…”
Section: Attractive Health Resourcementioning
confidence: 99%
“…15,30,40,41,43,45 Lastly, chatbots empowered women with relevant knowledge and enabled them to make their own health care decisions. 14,16,38…”
Section: Breaking Down Barriersmentioning
confidence: 99%
See 1 more Smart Citation